Viajando con Don Quijote en el siglo XXI - Odilíe Rojas-López (Universidad Nacional, Costa Rica, 2006)
Don Quixote has ridden with us for a long time now, and as if his fight against windmills were not enough, Don Quixote still has many more difficult situations to combat in the present times. Will the Knight of the Sad Figure accomplish this new deed? It is our challenge to find an answer to this inquiry. For this purpose, the author of this essay inserts the Knight of the Sad Figure in XXI century society. The author transforms the values, costumes and points of view of the times of the literary piece and establishes a series of relationships between the literary text, the main character and several current daily life situations. Don Quixote will certainly continue his fight against all the conditions we encounter nowadays. There is no doubt, then, that this knight still lives among us.